Addressing the Community/Public Health Nursing Shortage through a Multifaceted Regional Approach. Issue 6 (12th February 2014) - Young, Staci; Acord, Lea; Schuler, Sue; Hansen, Judith M.
Abstract Despite increasing needs resulting from emerging societal and health care issues, the number of trained community/public health (C/PH) nurses in the United States is facing a precipitous decline. Numerous factors contribute to this shortage including an aging workforce, a poorly funded public health system, inconsistencies in C/PH nursing educational approaches and opportunities, and a shortage of sites for clinical training. Determined to address the C/PH nursing shortage in their region, a consortium of public health professionals, university deans and faculty, and state nursing leaders in southeastern Wisconsin came together to address these issues from three perspectives: (a) curricular analysis and redesign, (b) expansion of clinical placement opportunities, and (c) paid community/public health nursing internships for seniors in baccalaureate nursing programs. This article outlines briefly the activities undertaken related to curricular review and clinical placements, and then describes in detail the approach, challenges and results of the senior internship program. Together, these programs produced long‐lasting results including an unprecedented level of collaboration between academic institutions and public health nursing professionals, the expansion of both traditional and nontraditional clinical sites in the region, and a transformative learning experience for seventeen senior nursing students from five participating universities.